GAMBARAN PELAKSANAAN CPR DENGAN LAGU SORRY - JUSTIN BIEBER TERHADAP KECEPATAN KOMPRESI DADA PADA PENOLONG AWAM - Rusdiana, Rusdiana; Wahid, Abdurahman (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022DO - 10.24843/coping.2022.v10.i05.p02, 2022)
Cardiopulmonary resuscitation (CPR) with a chest compression rate of 100 - 120 beats per minute is difficult without guidance. To maintain chest compression, the rhythm of a song can stabilize CPR rates of 100 - 120 beats per minute. The purpose of this study was to describe the implementation of CPR with the song Sorry-Justin Bieber on the speed of chest compression for lay rescuers. The method uses quantitative research with descriptive design with 30 respondents and uses probability sampling technique with random sampling . The instrument used is a QCPR Training application. Data were analyzed using descriptive statistic. The result of this research are compression speed have an average result of 109,83 beats / minute with a minimum speed of 100, maximum speed of 116, and standard deviation of 5,446. The success rate of respondents in performing chest compression is known to be 30 successful respondents. Hands Only CPR chest compression speed using the song Sorry - Justin Bieber had good results. Variations in the results of chest compression in this study were still within the range of 100 - 120 beats / minute in accordance with high quality CPR standards. This shows the picture that when performing Hands Only CPR with the song Sorry - Justin Bieber, the chest compression speed level will meet the right compression speed standard.